Energy Efficiency Analysis of Software Defined Network in Backbone Transmission Network of Kathmandu Valley of Nepal Telecom - Nyoupane, Jiwan; Jha, Ajay Kumar (Journal of Advanced College of Engineering and Management, 2018)
In the past, research scope of the ICT (Information and Communication Technology) was mainly based on performance and cost. The research community put insufficient effort to the energy consumed by ICTs and their impact on the environment. Current trends, such as increasing electricity costs, reserve limitations, and increasing emissions of carbon dioxide (CO2) are shifting the focus of ICT towards energy-efficient and well-performed solutions. Communication networks designed according to this energy efficiency criteria are called green networks. In this context, SDN architecture can have a significant role in reducing the energy consumption by decoupling control plane to a centralized controller that has global view of all underlying data plane devices. The research will be focused on energy efficiency analysis of Software Defined Network and financial possibilities for migration into SDN using LEAP taking the case study of Nepal Telecom!s backbone transmission network in Kathmandu region.